Hubungan Kebiasaan Belajar dengan Hasil Belajar Matematika Peserta Didik Kelas V Sekolah Dasar - Pangestu, Deviyanti; Lestari, Yulita Dwi; Surahman, Maman; Juwantara, Ridho Agung (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The problem in this research is the low mathematics learning outcomes of students. The purpose of this study was to determine a significant relationship between study habits with mathematics learning outcomes for grade V students at SDNegeri 4 Sumberejo in the academic year 2021/2022. This type of research is quantitative with ex-post facto correlation method. The population of this study was 55 students and sampling using a saturated sample technique. Data collection techniques used were questionnaire and documentation. Analysis of the data used is the product moment correlation and obtained a correlation of0,43 with contribution of 18,4% with moderate criteria. There is a significant relationship between learning independence and mathe matematics learning students outcomes for grade V students at SD Negeri 4 Sumberejo in the academic year 2021/2022.